Direct Compression of Cellulose and Lignin Isolated by a New Catalytic Treatment - Penkina, Anna (Springer US, 2013)
Tablet compression of softwood cellulose and lignin prepared by a new catalytic oxidation and acid precipitation method were investigated and compared with the established pharmaceutical direct compression excipients. Catalytic pretreated softwood cellulose (CPSC) and lignin (CPSL) were isolated from pine wood (Pinus sylvestris). The compaction studies were carried out with an instrumented eccentric tablet machine. The plasticity and elasticity of the materials under compression were evaluated using force-displacement treatment and by determining characteristic plasticity (PF) and elasticity (EF) factors. With all biomaterials studied, the PF under compression decreased exponentially as the compression force increased. The compression force applied in tablet compression did not significantly affect the elasticity of CPSC and microcrystalline cellulose (MCC) while the EF values for softwood lignins increased as compression force increased. CPSL was clearly a less plastically deforming and less compactable material than the two celluloses (CPSC and MCC) and hardwood lignin. CPSL presented deformation and compaction behaviour almost identical to that of lactose monohydrate. In conclusion, the direct tablet compression behaviour of native lignins and celluloses can greatly differ from each other depending on the source and isolation method used.